2003
DOI: 10.1001/archopht.121.10.1385
|View full text |Cite
|
Sign up to set email alerts
|

Chorioretinal Anastomosis After Radial Optic Neurotomy for Central Retinal Vein Occlusion

Abstract: To evaluate the incidence of chorioretinal anastomosis after radial optic neurotomy and to determine its effect on visual acuity and foveal thickness in patients with central retinal vein occlusion. Methods: We conducted a prospective, uncontrolled, interventional study of 14 patients with preoperative visual acuities below 20/125. Pars plana vitrectomy and radial optic neurotomy were performed. Fluorescein angiography and optical coherence tomography were used to monitor the evolution of macular edema. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
51
2
9

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(69 citation statements)
references
References 24 publications
(9 reference statements)
4
51
2
9
Order By: Relevance
“…However, we have no reliable data on how frequently spontaneous anastomosis occurs after an occlusion. Fuller et al [20 ]described a 46% incidence of spontaneous CRA after CRVO, and in the literature, the incidence of CRA after RON ranges from 42.9 to 60% [7, 21, 22]. In our study, 16 (57.1%) cases developed CRA after surgery compared to 2 (5.7%) controls.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…However, we have no reliable data on how frequently spontaneous anastomosis occurs after an occlusion. Fuller et al [20 ]described a 46% incidence of spontaneous CRA after CRVO, and in the literature, the incidence of CRA after RON ranges from 42.9 to 60% [7, 21, 22]. In our study, 16 (57.1%) cases developed CRA after surgery compared to 2 (5.7%) controls.…”
Section: Discussionsupporting
confidence: 53%
“…However, the reported positive influence of vitrectomy and removal of the posterior hyaloid in increasing the diffusion between retina and vitreous cavity should also be considered [16, 17]. Another recent hypothesis presented the development of CRA after RON and its consequent retinal blood flow improvement as the main therapeutic mechanism induced by neurotomy [7]. Regarding the importance of good preoperative visual acuity for a favorable visual outcome as shown by the CVOSG, preoperative BCVA of 0.32 or worse was our criterion to perform surgical treatment (RON) [8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, while improvements in visual acuity after RON have been confirmed by several other reports [61][62][63][64] , some studies found a resolution of macular edema that was not accompanied by an improvement in visual acuity in all eyes following RON [65,66] . On the other hand, some studies revealed that RON induce the development of retinochoroidal shunt vessels in 46.7-83.3% of patients and this may represent the mechanism of any beneficial effect this surgical procedure [67][68][69][70][71] . In addition, several authors suggested that the creation of RON involves a PPV and the beneficial effects of RON are due to this alone [72,73] .…”
mentioning
confidence: 99%